STUDI IDENTIFIKASI VIRUS KHV (KOI HERPES VIRUS) PADA IKAN KOI (CYPRINUS CARPIO): Identification Study of KHV Virus (Koi Herpes Virus) In Koi Fish (Cyprinus Carpio) - Juliasis Mayagi; Raismin Kotta; Kurniawati Kurniawati; I Gede Nano Septian (Yayasan Al-Amin Qalbu, 2023)
The purpose of this study was to find out how to identify KHV (koi herpes virus) in koi fish (cyprinus carpio) using the Polymerase Chain Reaction (PCR) method. This research is a survey research, namely identifying KHV in koi fish (Cyprinus carpio) using the PCR method. The results of this study indicated that the sample was declared negative for KHV if the band that appeared was parallel to 640 bp (internal DNA from the sample based on the manual kits and primer used), then the sample was free from HPI/HPIK KHV virus group. Whereas for samples that tested positive for KHV, the bands that appeared were parallel to 229 bp and 440 bp (the KHV Virus DNA composition used was based on the kits used). So the KHV found in infected Koi fish has DNA of 229 bp and/or 440 bp. This shows that the samples examined were positively infected with the KHV virus